Qualitative inquiry and research design - Creswell, John W (SAGE, 2013)
Previous ed. cataloged as: Qualitative inquiry & research design - 2007; Includes bibliographical references (p. 417-434) and indexes; Introduction -- Philosophical assumptions and interpretive frameworks -- Designing a qualitative study -- Five qualitative approaches to inquiry -- Five different qualitative studies -- Introducing and focusing the study -- Data collection -- Data analysis and representation -- Writing a qualitative study -- Standards of validation and evaluation -- "Turning the story" and conclusion